INDUKSI KALUS PASAK BUMI (Eurycoma longifolia Jack) MELALUI EKSPLAN DAUN DAN PETIOL - ROSMAINA, ROSMAINA; ZULFAHMI, ZULFAHMI; SUTEJO, PROBO; ULFIATUN, ULFIATUN; MAISUPRATINA, MAISUPRATINA (JURNAL AGROTEKNOLOGI, 2015)
One of the problem of Eurycoma longifolia Jack propagation was low germination percentage due to recalcitrant seeds and slow growth of seedling from cutting propagation. To overcome this problem is required propagation of Eurycoma longifolia via in vitro culture. The objective of this research was to know the effect of Auxin (2,4-D and NAA) and Cytokines (BAP and Kinetin)Â  on Eurycoma longifolia callus induction via leaf and petiole explants. In this study, we used plant growth regulator of 2,4 D, NAA, BAP and Kinetin in several levels.Â  The observed variables were appearing callus time, callus color and callus texture. The results of this study showed that MS medium supplemented with 1 ppm NAA+ 1 ppm BAP was able to induce callus formation in leaf explant for 6 months after culture. While MS medium supplemented with 1 ppm 2,4-D, 1 ppm BAP, combination of 2,4-D and Kinetin and combination of 2,4-D and BAP can induce callus formation from petiole. All the callus formation has yellow color and yellow brown color. The petiole explant that is grown in MS medium supplemented with 1 ppm BAP induced of callus in short time (18 days after culture).